Perlindungan Hukum Terhadap Pemegang Hak Cipta Karya Sinematografi Atas Situs Penyedia Streaming Gratis Di Media Internet - Evi Pradita Ismail; Theresia Nolda Agnes Narwadan; Muchtar Anshary Hamid Labetubun (PATTIMURA Law Study Review, 2023)
ABSTRACT: The development of the age is directly proporent to the development of life-sustaining technologies such as the Internet, while cyberspace may also present special drawback to copyright. On the Internet countless free streaming websites that disseminate cinematography (movies) without the permission of copyright holders which have violated the copyright owners' economic rights of duplicating, distributing and using the copyright holder without permission, Research shows that protection against copyright holders by cinematography on the Internet's free streaming site consists of preventive law of surveillance, coordination, and cooperation with the creation, dissemination and surThe research method used was normative-yuridis, using the problem approach of legislation and conceptual approach, the source of the legal materials used in the primary, secondary and tertiary materials. The technique for collecting legal materials used was the collecting of judicial material, which was analyzed using qualitative methods. Veillance of the ACTS of cinematography and the recording of creation. As well as the repressive protection by closing or blocking free streaming sites on Internet media by kominfo, the repressive protection is in the form of temporary judges, penalties for damages and criminal proceedings. As a result of the law that receives free streaming site owners is sanctioned by paying damages to copyright holders and criminal penalties of prisons and penalties.